Translating GRAFCET Charts into C++ Code for Embedded Control Applications - SOGBOHOSSOU, MEDESU; HOUNKPEVI, CLEMENT (My University, 2020)
For the implementation of an embedded application, the specification phase of the system allows it to be validated. A GRAFCET chart (IEC 60848) may be the modelling language for this kind of systems. This paper introduces the translation of GRAFCET chart into a code for embedded platforms in order to perform control applications. Here, GRAFCET charts are edited with Jgrafchart software, which returns a XML file that is used to translate useful information of the chart into code in C++ language, particularly for mbed microcontrollers. The notable elements of GRAFCET that we consider are steps (and their corresponding actions), transitions, variables and especially elements that take into account the hierarchical aspect in GRAFCET such as macro-steps and enclosing steps.
Keywords: GRAFCET (IEC 60848); code generation; control applications; mbed platform; Jgrafchart